Settings, Quantification, and Statistical Analyses beyond p‐Values for Arabidopsis Ethylene Responses. Issue 8 (13th August 2019) - Lu, Jian; Wen, Chi‐Kuang
Abstract: Ethylene is a gaseous plant hormone and plays various roles in plant growth and development. Studies on ethylene‐induced responses have advanced the knowledge about ethylene signaling and effects of its interactions with other plant hormones and with biotic and abiotic cues. Degrees of the ethylene response can be quantified on the basis of the "seedling triple‐response assay" that primarily measures the hypocotyl and/or root lengths of etiolated Arabidopsis seedlings. Different laboratories perform the assay differently, possibly with various degrees of arbitrariness, and experimental results across independent studies can hardly be shared and compared. An optimal and standardized protocol for the setting of ethylene treatment may facilitate data sharing, reproducing, and new findings. Data collected from experiments are quantified and analyzed statistically to support scientific inference. On the other hand, erroneous statistical practices are criticized for muddling scientific inference, leading to poor reproducibility and false results. Grasping the basic concepts of statistics may avoid erroneous practices and inference. Different settings for ethylene treatment prevalently adapted in the field are compared in this study, analyzed statistically to explain how the settings may affect the outcome, and a standardized conduct for the seedling triple‐response assay is proposed. Abstract : Sampling and experimental settings that affect the measurement of degrees of the ethylene response, in terms of accuracy and reproducibility, are statistically compared, and a standardized operation procedure to optimize the assay is proposed to facilitate data analyses across studies. Basic concepts for statistical analyses are explained to aid the appropriate use of statistical indexes in scientific reasoning.